2021
DOI: 10.1063/5.0075391
|View full text |Cite
|
Sign up to set email alerts
|

Ferroelectric Hf0.5Zr0.5O2 thin films deposited epitaxially on (110)-oriented SrTiO3

Abstract: Hf0.5Zr0.5O2 (HZO) thin films have been deposited on (110)-oriented SrTiO3 (STO) substrates buffered with epitaxial La0.7Sr0.3MnO3 (LSMO) by pulsed laser deposition. The HZO/LSMO/STO heterostructures show smooth surface and clear interface. It is observed that ferroelectric orthorhombic HZO is enhanced, as non-polar tetragonal HZO is suppressed with the increasing LSMO thickness or decreasing HZO thickness. Completely orthorhombic HZO films are achieved with desired LSMO and HZO thickness. These HZO films are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 44 publications
1
8
0
Order By: Relevance
“…The ϕ angle differences between the 2 spots within each set, defined as α, are several degrees only. These pole figure patterns are similar to the previously reported ones in HZO/LSMO/STO(110) [34,35] but distinct from those measured from the HZO/LSMO(001) films, [25] in which the 12 HZO {-111} diffraction spots are separated by a constant ϕ≈30°. In addition, the pole figure also shows 4 sharp and bright spots at χ≈60°, which can be assigned to the {011} C diffraction spots of the (110) C -oriented substrates or LSMO films (See detailed discussion in Figure S8, Supporting Information).…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…The ϕ angle differences between the 2 spots within each set, defined as α, are several degrees only. These pole figure patterns are similar to the previously reported ones in HZO/LSMO/STO(110) [34,35] but distinct from those measured from the HZO/LSMO(001) films, [25] in which the 12 HZO {-111} diffraction spots are separated by a constant ϕ≈30°. In addition, the pole figure also shows 4 sharp and bright spots at χ≈60°, which can be assigned to the {011} C diffraction spots of the (110) C -oriented substrates or LSMO films (See detailed discussion in Figure S8, Supporting Information).…”
Section: Resultssupporting
confidence: 88%
“…Recent publications indeed suggested that the FE polarization of HZO films grown on STO(110) substrates can be enhanced compared to the films grown on STO(001) substrates. [5,34,35] However, the detailed correlation between structural symmetry, FE domain configuration, and ferroelectricity in HZO films under the anisotropic strain remains elusive.…”
Section: Introductionmentioning
confidence: 99%
“…This has permitted to study intrinsic endurance [17], switching dynamics [18] and tunneling current contributions [19] in films of high crystalline quality, eventually allowing to better control their properties [20]. In addition, it has been recently shown that the ferroelectric phase can be grown epitaxially on (110) and (111)-oriented SrTiO 3 substrates [21][22][23]36].…”
Section: Introductionmentioning
confidence: 99%
“…17 Very recently, the epitaxial growth of orthorhombic Hf 0.5 Zr 0.5 O 2 (HZO) on (110)-oriented LSMO electrodes has also been reported. 18,19 Hf 0.5 Zr 0.5 O 2 (HZO) films or other HfO 2 doped compounds grown on LSMO(001) or LSMO(110) are (111) oriented, while the ferroelectric dipoles are oriented along the [001] direction.…”
Section: Introductionmentioning
confidence: 99%